Executive function is an important consideration for coping strategy use in people with multiple sclerosis. Issue 8 (14th September 2017) - Grech, Lisa B.; Kiropoulos, Litza A.; Kirby, Katherine M.; Butler, Ernest; Paine, Mark; Hester, Robert
ABSTRACT: Introduction : Executive function deficits are prevalent in people with multiple sclerosis (PwMS), and PwMS use less adaptive coping than healthy controls. This cross-sectional study assessed whether there is a relationship between executive function and coping in PwMS. Method : One hundred and seven participants with relapsing remitting or secondary progressive MS ( n  = 83 and 24, respectively; age M  = 48.8 ± 11.1 years) completed measures of coping and executive function. Results : A positive relationship was found between verbal fluency and use of active, emotional, and instrumental social support coping, and total executive function and substance abuse coping. There was a negative relationship between coping strategies and core (social support, acceptance, religion, restraint, and total coping), higher order (denial and humor), and total executive function indices (acceptance, religion, behavioral disengagement, denial, and total coping). Conclusion : These directional differences provide support for the importance of specific executive functions in coping strategy utilization. Understanding these relationships will assist psychologists and neuropsychologists with patient psychoeducation, adaptive coping strategy intervention and management for PwMS with reduced executive function ability.